Prometheus Bound. - Aeschylus (Greek tragedy in new translations., 1975)
For readers accustomed to the relatively undramatic standard translations of Prometheus Bound, this version by James Scully, a poet and winner of the Lamont Poetry Prize, and C. John Herington, one of the world's foremost Aeschylean scholars, will come as a revelation. Scully and Herington accentuate the play's true power, drama, and relevance to modern times. Aeschylus originally wrote Prometheus Bound as part of a tragic trilogy, and this translation is unique in including the extant fragments of the companion plays.